A seven-year retrospective study of a single center in Xinjiang：clinical features of pregnancy-related acute kidney injury - Li Su-hua; Huang Xuan; Li Meng-xuan; Chu Xue-qian; Ayi-Tudi Mire; Li Xin-sai; Jiang Xu-yan (Linchuang shenzangbing zazhi)
ObjectiveTo explore the epidemiological and clinical characteristics of pregnancy-related acute kidney injury （PR-AKI） at a single center in Xinjiang.MethodsThrough accessing the inpatient network case system of First Affiliated Hospital of Xinjiang Medical University，the authors retrospectively reviewed clinical data of pregnant women hospitalized from January 2013 to November 2020.ResultsA total of 157 PR-AKI patients were recruited with an overall detection rate of 0.22%.The top three causes of PR-AKI were hypertension in pregnancy （52.9%），acute fatty liver of pregnancy （11.5%） and postpartum hemorrhage （10.2%）.Single factor Logistic regression analysis revealed that diastolic blood pressure （OR=1.022，95%CI：1.005-1.040），systolic blood pressure （OR=1.013，95%CI：1.001-1.026），serum potassium （OR=1.942，95%CI：1.066-3.538），urea nitrogen （OR=1.331，95%CI：1.200-1.476），blood creatinine （OR=1.033，95%CI：1.200-1.476） and total bilirubin （OR=1.010，95%CI：1.001-1.019） were risk factors for severe PR-AKI.The correlation coefficient between neonatal birth weight and maternal gestational age was the largest while correlation coefficient with prothrombin time was the smallest.ConclusionFor lowering the incidence of PR-AKI at grassroots areas，clinicians may strive to promote healthy lifestyles during pregnancy，conduct regular and comprehensive obstetric examinations and perfect screening of high-risk pregnant women to reduce adverse pregnancy outcomes.